Keunggulan dan Spesialisasi Ekonomi Wilayah di Kabupaten Wonosobo, 2000-2009 (Pendekatan Model Shift-Share Esteban Marquillas) - Lio Andi Prasetia; Neni Widayaningsih; Emmy Saraswati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2011)
This research aims to know the competitive advantage, specialize, and sektors allocation effect in Wonosobo Regency along the research period, especially on agriculture sektor. The Shift Share Esteban Marquillas calculation result shows that Wonosobo is specialized on agriculture sektor that supported by compatible land and climate condition for agriculture, but it has no competitive advantage, thus agriculture sektor allocation effect have a negative value and defined by no competitive advantage but specialized. Based on the negative value of agriculture sektor allocation effect and defined by no competitive advantage but specialized, thus it can be a priority in developing Wonosobo by improving agriculture sektor productivity so they can compete with other regions, for instance optimizing socialization to farmer (gapoktan), giving information about market access, using superior seeds, adopting necessary technology, stabilizing price and distributing fertilizer to farmer. Keywords: advantage, specialize, shift share esteban marquillas